2022
DOI: 10.31219/osf.io/r349e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Spectral Nature of COVID-19 and other Infectious Diseases

Abstract: The logically deduced conception of the pathological manifestations that follow infection with SARS-CoV-2 as manifestations of a single transmissible disease that this coronavirus causes disagrees with experience and poses insurmountable difficulties. But a new concept of the nature of infectious diseases emerges upon illustrating reality with a superior method of obtaining knowledge which makes logical deductions only to obtain consequences which must agree perfectly with experience if indeed our hypotheses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…And this consequence yields the prediction that when immunological conditions that protect us from deadly outcomes of Monkeypox and Ebola disappear in a sufficiently large proportion of the populations on these continents and the causes of such deadly outcomes are present at the time of such disappearance, such deadly outcomes will appear catastrophically and decimate such populations if we do not elucidate such conditions that give rise to immunity before such a time. 6 And it ultimately follows that even when pathogens such as the monkeypox virus and the Ebola virus are absent at such a time but causes of the diseases that are immunologically linked with the diseases that such pathogens cause, which may include cancers, are present, outcomes such 6 as malignancies, which are already difficult to treat in spite of the many treatments that are available, will become so widespread within a short period of time that we will assume, as we did when Devil Facial Tumor Disease appeared catastrophically in Tasmanian devils, 6 that they are being rapidly transmitted when they are in reality spectral diseases 5 which can appear in every single member of the population at the same time if immunological conditions disappear in the entire population at the same time. This might be the mechanism by which certain evolutionary forms became irreversibly decimated and ultimately rendered extinct.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…And this consequence yields the prediction that when immunological conditions that protect us from deadly outcomes of Monkeypox and Ebola disappear in a sufficiently large proportion of the populations on these continents and the causes of such deadly outcomes are present at the time of such disappearance, such deadly outcomes will appear catastrophically and decimate such populations if we do not elucidate such conditions that give rise to immunity before such a time. 6 And it ultimately follows that even when pathogens such as the monkeypox virus and the Ebola virus are absent at such a time but causes of the diseases that are immunologically linked with the diseases that such pathogens cause, which may include cancers, are present, outcomes such 6 as malignancies, which are already difficult to treat in spite of the many treatments that are available, will become so widespread within a short period of time that we will assume, as we did when Devil Facial Tumor Disease appeared catastrophically in Tasmanian devils, 6 that they are being rapidly transmitted when they are in reality spectral diseases 5 which can appear in every single member of the population at the same time if immunological conditions disappear in the entire population at the same time. This might be the mechanism by which certain evolutionary forms became irreversibly decimated and ultimately rendered extinct.…”
mentioning
confidence: 91%
“…Upon illustrating this reality in which such pathological manifestations are brought about in the infected after painstakingly, for over a decade, developing the method of obtaining knowledge which is superior to the one that makes logical deductions from observations, 4 I found that the nature of the disease that the pathogen causes alone is not what determines the severity of the pathological manifestations that appear in the infected but rather the nature of those that appear among the diseases in the immunological spectrum of this infectious disease. 5 The diseases in the immunological spectrum of the disease the pathogen causes are those diseases which co-occur with this infectious disease when their causes are present alongside the pathogen at the time of the disappearance of the conditions that permit immunological mechanisms to obstruct the single pathway through which diseases in this spectrum are brought about by pathological mechanisms in response to the influence of the pathogen and such causes that are immunologically linked with it.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This spectral disease concept of such diseases that are caused by those infectious biological entities that we refer to as pathogens describes the pathological manifestations that appear in the infected as an outcome of the concomitant appearance of different diseases in a spectrum that includes the disease that the pathogen causes upon the disappearance of the conditions that permit immunological mechanisms to obstruct the single pathway through which pathological mechanisms respond to the influence of the pathogen and the different causes.. 4 It is this spectral disease concept which has found representation in the observations our clinicians have made during the current pandemic, outcomes which include the multiorgan failure which causes death in severe COVID-19 cases 5 and as predicted in another paper on the current monkeypox outbreaks outside of Africa 6 where a less virulent monkepox virus was logically deduced to be spreading, 7 the Encephalitis that caused 3 deaths in Spain and India and the comorbidities that caused the death of a Brazilian patient with lymphoma. 8 Such comorbidities were reported to have aggravated the patient's condition 8 in the absence of the knowledge of the spectral concept of such severe pathological manifestations as those that caused these monkeypox deaths, one which describes them as manifestations of different diseases which belong to the same spectrum as the infectious disease that the monkeypox virus causes.…”
mentioning
confidence: 99%
“…26 And one of the results of this investigation is that the pathological manifestations that appear in the infected are manifestations of the infectious disease and other diseases which appear to be manifestations of a single disease 25 because such spectral manifestations are brought about concomitantly upon the disappearance of the conditions that permit immunological mechanisms to obstruct the single pathway through which pathological mechanisms respond to the influence of the pathogen and the causes of the diseases in the immunological spectrum of the infectious disease. 27 One of the consequences of this result is that upon the reappearance of the conditions that permit immunological mechanisms to obstruct the single pathway through which pathological mechanisms respond to the pathogen and the causes of the diseases in the immunological spectrum of the infectious disease, the manifestations of those that are present among such disease will begin to disappear simultaneously. 25 Upon comparing this consequence with the data of experience, the most significant among the observations that correspond perfectly with it are those that involve the concomitant disappearance of the manifestations of infectious diseases and the diseases that co-manifest with it to produce clinical outcomes that include evidence of malignant cancer.…”
mentioning
confidence: 99%